How Helpful Are Online English Learners' Dictionaries in Dealing with Misspellings? - Lew, Robert; Mitton, Roger (My University, 2012)
This study looks at how well the leading monolingual English learners’ dictionaries in their online versions cope with misspelled words as search terms. Seven such dictionaries (Longman Dictionary of Contemporary English, free online version; Longman Dictionary of Contemporary English, premium subscription version; Merriam-Webster's English Learner's Online Dictionary; Macmillan English Dictionary Online; Cambridge Advanced Learner's Dictionary; Oxford Advanced Learner’s Dictionary; and Google English Dictionary) are tested on a corpus of misspellings produced by Polish, Japanese, and Finnish learners of English. The performance of the dictionaries varies widely, but is in general disappointing. In a large proportion of cases, the dictionaries fail to supply the intended word, and when they do, they do not place it at the top of the list of suggested alternatives. Results are then compared with those from one year ago for the same dictionaries and the same misspellings. A detailed analysis follows, identifying some of the mechanisms behind the failures in identifying and correcting misspellings. The success rates of the dictionaries are compared with that of an experimental context-free spellchecker developed by the second author, and the spellchecker is found to be markedly superior. The data are subjected to a cluster analysis to see if the dictionaries can be grouped based solely on their performance. The article concludes with suggestions on how to improve the performance of the spellchecking facilities in online dictionaries.
This is a Pre-Print: An unrefereed manuscript version of an article, as submitted for review in a journal. This pre-print version is much more substantial than the final published version. The final published version has appeared as: Lew, Robert and Roger Mitton 2012. `Online English Learners´ Dictionaries and Misspellings: One Year On.´ International Journal of Lexicography. DOI: 10.1093/ijl/ecs016
Keywords: Online dictionaries; English; spelling; spelling correction; spelling errors; misspelling; access